Strain effect on SnS2 nanoribbons: Robust direct bandgap of zigzag-edge and sensitive indirect semiconductor with armchair-edge states. (November 2017) - Liu, Yaming; Qiu, Guizhen; Kong, Dechuan; Hu, Bo; Li, Yongfeng; Su, Jianxiu; Xia, Congxin
Abstract: First-principles calculations are used to study the electronic properties and strain effect on the SnS2 nanoribbons with zigzag- and armchair-terminated edge states. Theoretical results show that bandgaps of both types of nanoribbons decrease monotonically with the increasing ribbon width. The indirect bandgap characteristic is reserved in ANRs, while ZNRs turn into direct bandgap semiconductors. Applying the uniaxial strain, the bandgap of 13-ANR is sensitive and can be modified significantly, while the 8-ZNR exhibits a 2.1eV robust direct bandgap at X point. Our calculations indicate that zigzag-edged SnS2 nanoribbons can be potential candidates in optoelectronics and photocatalyst. Graphical abstract: Highlights: Electronic properties of two types of nanoribbons of SnS2 were investigated by DFT. Bandgaps of zigzag-NR turn into direct and robust under strain. Indirect bandgap of armchair-NR is reserved and sensitive to strain. Similar variation trends of VBM and CBM contribute to the robust characteristics.